2004
DOI: 10.1002/pamm.200410235
|View full text |Cite
|
Sign up to set email alerts
|

Deformation von Belebtschlammflocken in Dehnströmungen

Abstract: Im vorliegenden Beitrag wird die Deformation von Belebtschlammflocken (BSF) in einer Dehnströmung betrachtet. Dazu werden BSF aus einer kommunalen Kläranlage in einem entsprechend geformten Kanal einer laminaren, dehnungsbehafteten Strömung ausgesetzt. Eine Dehnung der Flocken sowie Desintegration größerer Flockenaggregate durch diese mechanische Belastung können nachgewiesen werden. Diese strömungsinduzierte Desintegration erlaubt eine Vergrößerung der aktiven Oberfläche und verhindert eine metabolische Limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In comparison, Höfer et al (2004) observed elongation of the CAS in the range of˙ = 0.2. From the current work we assume that elongation rate up to˙ = 1 affects significantly the granulation process.…”
Section: Comparison Of Experimental With Simulation Results In Sbrmentioning
confidence: 81%
“…In comparison, Höfer et al (2004) observed elongation of the CAS in the range of˙ = 0.2. From the current work we assume that elongation rate up to˙ = 1 affects significantly the granulation process.…”
Section: Comparison Of Experimental With Simulation Results In Sbrmentioning
confidence: 81%